Distributed Campus Time Attendance System: k-Kedatangan - Nasrudin, Abd Shukor; Nor Shubaily, Khamis; Mohd Noorulfakhri, Yaacob (International Exhibition of Inventions, 2010)
International Exhibition of Invention of Geneva 2006, 5th - 9th April 2006 was held at Palexpo, Geneva, Switzerland.